(untitled) (Bangladesh Journal of Anatomy, 2015)
Context : It has long been customary among anatomists, anthropologists and forensic experts to judge the sex of the skeletal material by non-metric observations. Afterward the study of sexual divergence has been based upon actual measurements in different bones. The study in relation to metrical data on bone is very few in our country. The study was planned to observe the differences of sacra between male and female in respect to measurement of alar length and auricular index of sacrum. The findings of this study might be useful in providing morphometrical data that can be used by anatomists, forensic experts, anthropologists, orthopedic surgeons and neurologists for proper initiative in their respective fields. Materials and Methods: A cross-sectional, analytical type of study was performed in the department of Anatomy, Dhaka Medical College, Dhaka from January 2011 to December 2011. A total of 172 (one hundred seventy two) adult human dry sacra of unknown sex was assessed. The study samples were distributed in male and female sex groups by discriminant function analysis. All the samples were studied morphologically. Length of ala and auricular surface were measured with the help of digital slide calipers. Results: The mean length value of ala was greater in female than male (P<0.001). The difference between the mean value of alar index in male and female was significant (P >0.05). The mean value of auricular index was higher in male than female and the difference was statically significant (P<0.001). Conclusion: The sacrum can be used for sexual dimorphism as is usual in anthropological work. The knowledge of alar length and auricular index of sacrum is essential in medico-legal practice for sex determination of an individual. DOI: http://dx.doi.org/10.3329/bja.v12i1.22613 Bangladesh Journal of Anatomy, January 2014, Vol. 12 No. 1 pp 17-21